Television Advertising Effectiveness in Mediating Advertising Creativity and Advertising Frequency Influence toward Customer Purchase Intention - Saputro, Yogi; Prihandono, Dorojatun (Management Analysis Journal, 2018)
The purpose of this study is to examine the direct and indirect influence of television advertising creativity and advertising frequency on purchase intention using advertising effectiveness as a mediation variable. Purchase intention influencing customers to purchase decision. Without any purchase intention, customer will not visit to e-commerce site. The respondents in this study were customer e-commerce JD.id in Semarang City. The sample in this study is intended as the representative of total population,116 sample who were taken by purposive sampling technique. This research utilized path analysis method with SmartPLS 3.0 program. Based on the hypothesis test, the results show that the advertising creativity was significantly has positive effect on purchase intention, but advertising frequency has no significant effect on purchase intention. In addition, advertising effectiveness significantly have positive effect on purchase intention. Mediation test shows that advertising effectiveness mediates the effect of the advertising creativity and advertising frequency on customer purchase intention.